Synthesis and Development of N-2,5-Dimethylphenylthioureido Acid Derivatives as Scaffolds for New Antimicrobial Candidates Targeting Multidrug-Resistant Gram-Positive Pathogens - Povilas Kavaliauskas; Birutė Grybaitė; Rita Vaickelionienė; Birutė Sapijanskaitė-Banevič; Kazimieras Anusevičius; Agnė Kriaučiūnaitė; Gabrielė Smailienė; Vidmantas Petraitis; Rūta Petraitienė; Ethan Naing; Andrew Garcia; Vytautas Mickevičius (MDPI AG, 2023)
The growing antimicrobial resistance to last-line antimicrobials among Gram-positive pathogens remains a major healthcare emergency worldwide. Therefore, the search for new small molecules targeting multidrug-resistant pathogens remains of great importance. In this paper, we report the synthesis and in vitro antimicrobial activity characterisation of novel thiazole derivatives using representative Gram-negative and Gram-positive strains, including tedizolid/linezolid-resistant S. aureus, as well as emerging fungal pathogens. The 4-substituted thiazoles 3h, and 3j with naphthoquinone-fused thiazole derivative 7 with excellent activity against methicillin and tedizolid/linezolid-resistant S. aureus. Moreover, compounds 3h, 3j and 7 showed favourable activity against vancomycin-resistant E. faecium. Compounds 9f and 14f showed broad-spectrum antifungal activity against drug-resistant Candida strains, while ester 8f showed good activity against Candida auris which was greater than fluconazole. Collectively, these data demonstrate that N-2,5-dimethylphenylthioureido acid derivatives could be further explored as novel scaffolds for the development of antimicrobial candidates targeting Gram-positive bacteria and drug-resistant pathogenic fungi.